2015
DOI: 10.1038/srep14962
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and Caloric Restriction in a Marine Planktonic Copepod

Abstract: Planktonic copepods are a key group in the marine pelagic ecosystem, linking primary production with upper trophic levels. Their abundance and population dynamics are constrained by the life history tradeoffs associated with resource availability, reproduction and predation pressure. The tradeoffs associated with the ageing process and its underlying biological mechanisms are, however, poorly known. Our study shows that ageing in copepods involves a deterioration of their vital rates and a rise in mortality as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 58 publications
5
39
2
Order By: Relevance
“…While LDEs are known contributors to spontaneous proteome damage during organismal ageing, any investigation of the potential for carbonyl scavengers to afford health benefits by suppressing such damage are complicated by the complexities and cost of performing lifespan extension studies in mammalian species. In recent times, the emergence of experimental approaches involving "simple" model organisms with short lifespans have allowed novel investigations of the effects of carbonyl-scavengers on the functional deficits that accompany ageing [79,80].…”
Section: Novel Cytoprotective Properties Of Hydralazinementioning
confidence: 99%
“…While LDEs are known contributors to spontaneous proteome damage during organismal ageing, any investigation of the potential for carbonyl scavengers to afford health benefits by suppressing such damage are complicated by the complexities and cost of performing lifespan extension studies in mammalian species. In recent times, the emergence of experimental approaches involving "simple" model organisms with short lifespans have allowed novel investigations of the effects of carbonyl-scavengers on the functional deficits that accompany ageing [79,80].…”
Section: Novel Cytoprotective Properties Of Hydralazinementioning
confidence: 99%
“…Zooplankton ecology is most frequently studied from the perspective of feeding, growth, and reproduction (Alcaraz and Saiz ). Mortality, however, has received comparatively less attention despite its importance to population dynamics (Verity and Smetacek ; Hirst and Kiørboe ; Saiz et al ). Predation is considered one of the major sources of mortality in zooplankton (Hirst and Kiørboe ).…”
mentioning
confidence: 99%
“…Later, Saiz et al . 13 , studying the closely related copepod species Paracartia grani , found that the deterioration of vital rates and rise in mortality associated with age (true senescence) were related to an increase in oxidative damage (lipid peroxidation). This increase in oxidative damage was accompanied by a rise in the relative content of the fatty acid 22:6(n-3), an essential component of cell membranes that increases their susceptibility to peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Saiz et al . 13 reported the first evidence of the effects of caloric restriction in marine copepods. As in many other animal models, caloric (food) restriction lowered age-specific mortality rates and increased survival times of the calanoid copepod P. grani .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation